Correlation of Adequate Urea Reduction Rate (URR) with the Degree of Uremic Pruritus and Sleep Quality in Chronic Kidney Disease Patients Undergoing Hemodialysis - Sri Rahayu; Ni Wayan Rahayu Ningtyas; Rukmini Syahleman (Indonesian Journal of Global Health Research, 2025)
Chronic kidney disease (CKD) patients undergoing hemodialysis are at risk of dialysis inadequacy, which can be assessed through the Urea Reduction Rate (URR) parameter. A low URR reflects a suboptimal hemodialysis process, leading to the accumulation of uremic toxins in the body. This inadequacy can trigger complications such as uremic pruritus, a chronic itching sensation that disrupts comfort and reduces the patient's quality of life. Furthermore, the accumulation of toxic substances due to inadequate URR impacts sleep quality, characterized by difficulty falling asleep, frequent awakenings, and restless sleep. These two conditions are often overlooked in clinical practice, yet they significantly contribute to the decline in the physical and psychosocial well-being of hemodialysis patients. The study aims to analyze the Correlation of Adequate Urea Reduction Rate (URR) with the Degree of Uremic Pruritus and Sleep Quality in Chronic Kidney Failure Patients Undergoing Hemodialysis. This study used a correlational analytical design with a cross-sectional approach. The sample consisted of 50 respondents of chronic kidney failure patients undergoing hemodialysis using a purposive sampling technique. URR data were obtained from laboratory records and using the URR calculation formula using the formula URR = 100 × (1 - C1/C0), while data on the degree of pruritus were collected using a Numerical Rating Scale (NRS) questionnaire and sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). Data analysis was performed using the Spearman Rank test to determine the relationship between variables. The results of the study showed that there was a significant relationship between URR and the degree of uremic pruritus p value 0.001 (p < 0.05) with a Correlation Coefficient value of 0.628 meaning a strong level of relationship, and there was a significant relationship between URR and the sleep quality of respondents undergoing hemodialysis p value 0.001 (p < 0.05) with a Correlation Coefficient value of 0.656 meaning a strong level of correlation. Dialysis adequacy measured by URR has an important role in reducing uremic pruritus symptoms and improving sleep quality in CKD patients.